2017
DOI: 10.6007/ijarbss/v7-i4/2782
|View full text |Cite
|
Sign up to set email alerts
|

Malaysian Youth Perception on Cyberbullying: The Qualitative Perspective

Abstract: Cyberbullying is not an emerging new problem and number of international scholars have placed their interest on the issue. In Malaysia, although the number of cyberbully studies are increasing, however, studies on cyberbullying in particular from the qualitative perspective is still lacking. This has geared the current study to prod youth perception on cyberbullying from the qualitative perspective. Their perceptions on cyberbullying were based on six main aspects, namely their comprehension of it, sources of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
(30 reference statements)
0
3
0
Order By: Relevance
“…Qualitative research in this domain would allow for a more holistic understanding of the experience and perception of key stakeholders involved in the cyberbullying world ( Tracy, 2013 ). While purely qualitative methods in cyberbullying research are increasing, many studies focus on the youth perspective of perceptions and the experiences of cyberbullying itself (e.g., Vandebosch and Van Cleemput, 2008 ; Evans et al, 2016 ; Ghazali et al, 2017 ; Chia-Wen et al, 2019 ). Critical key informants and stakeholders who have experience managing cyberbullying issues on a regular basis may be the key to adequately addressing, designing, and implementing prevention strategies to reduce cyberbullying.…”
Section: Introductionmentioning
confidence: 99%
“…Qualitative research in this domain would allow for a more holistic understanding of the experience and perception of key stakeholders involved in the cyberbullying world ( Tracy, 2013 ). While purely qualitative methods in cyberbullying research are increasing, many studies focus on the youth perspective of perceptions and the experiences of cyberbullying itself (e.g., Vandebosch and Van Cleemput, 2008 ; Evans et al, 2016 ; Ghazali et al, 2017 ; Chia-Wen et al, 2019 ). Critical key informants and stakeholders who have experience managing cyberbullying issues on a regular basis may be the key to adequately addressing, designing, and implementing prevention strategies to reduce cyberbullying.…”
Section: Introductionmentioning
confidence: 99%
“…Online violence and cyberbullying in OSN keep growing each day. According to Ghazali et al, 2017, Malaysia have recorded an increment from 2013 (55.6%) to 2015 (62.3%) for cyber-bullying cases among the Malaysian youth [1]. Mohammad (2021) reported that three out of every ten Malaysian adolescents have been bullied, as stated by United Nations Children's Fund (UNICEF) [2].…”
Section: Introductionmentioning
confidence: 99%
“…Research on cyber aggression-victimization have been reported in Europe, the United States of America and Asian countries. However, research in Malaysia has focused mainly on cyberbullying (Abu Bakar, 2013;Balakrishnan, 2015;Faryadi, 2011;Ghazali et al, 2017;Teimouri et al, 2014;Yusuf et al, 2018). As far as the researchers are concerned, there is limited, or no study conducted on cyber aggression or cyber victimization in Malaysia.…”
Section: Introductionmentioning
confidence: 99%